Skin capillary endothelial cells form a network of spatiotemporally conserved Ca 2+ activity - Anush Swaminathan; David G. Gonzalez; Catherine Matte-Martone; Fei Xu; Deandra Simpson; Jessica L. Moore; Zhongqi Lin; Ushnish Rana; David Monedero-Alonso; Julia J. Mack; Chen Yuan Kam; Valentina Greco (Proceedings of the National Academy of Sciences, 2026)
Ca 2+ signaling and its regulation are important for endothelial cell (EC) function and signaling. Yet, the spatiotemporal organization of Ca 2+ activity and its regulation across a vascular plexus is poorly understood in an in vivo mammalian context. To overcome this gap in knowledge, we developed an intravital imaging approach to resolve Ca 2+ activity with single-cell resolution in skin vasculature of adult mice via multiphoton microscopy. Here, we tracked thousands of Ca 2+ events in the skin capillary plexus during homeostasis and observed signaling heterogeneity between ECs, with just over half displaying Ca 2+ activity at any given time. Longitudinal tracking of the same mice revealed that the same capillary ECs maintain Ca 2+ activity over days to weeks. Interestingly, activity dynamics, such as frequency and event duration, are not conserved at a single-cell level but are maintained at an EC population level. Molecularly, conditional deletion of the gap junction protein Connexin 43 (Cx43cKO) in ECs leads to a subset of ECs displaying sustained Ca 2+ activity, biasing signaling dynamics of the whole network toward chronically persistent activity over time. Sustained capillary Ca 2+ activity results in vascular permeability and flow dysregulation. Last, through pharmacological targeting of known agonists/antagonists, we showed that inhibition of L-type Voltage Gated Ca 2+ channels non-cell-autonomously restores Ca 2+ activity, blood flow, and barrier function in Cx43cKO mice. Collectively, our work provides insight into the spatial and temporal characteristics, extent, and regulation of Ca 2+ activity in skin capillaries of live mice.